A long-lived iridium(iii) chemosensor for the real-time detection of GHB. Issue 15 (3rd April 2017) - Wang, Wanhe; Dong, Zhen-Zhen; Yang, Guanjun; Leung, Chung-Hang; Lin, Sheng; Ma, Dik-Lung
Abstract : In this work, a long-lived iridium(iii ) chemosensor1 has been synthesized for the detection of GHB. The luminescence signal of iridium(iii ) complex1 could also be distinguished from strongly fluorescent media using time-resolved emission spectroscopy. Abstract : Gamma-hydroxybutyric acid (GHB) is a commonly used "date rape" drug in drug-facilitated sexual assaults (DFSA) due to its low price and ready availability, and it is more quickly excreted from the human body than other drugs. Therefore, the development of a real-time detection method for GHB could help facilitate law enforcement agencies in tackling DFSA. In this work, a long-lived iridium(iii ) chemosensor1 has been synthesized for the switch-off detection of GHB. Upon addition of GHB to an aqueous solution of the iridium(iii ) complex1, a significant luminescence quenching occurred that could be observed by the naked eye under UV illumination. The luminescence signal of the iridium(iii ) complex1 could also be distinguished from strongly fluorescent media using time-resolved emission spectroscopy.